Hubungan Self Compassion dengan Mathematical Resilience Mahasiswa Pendidikan Matematika - Rahmah Badiatuzzulfa; Netriwati Netriwati; Anggun Fournicia; Ayu Aprina; Mella Aby Valeri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Students' ability to face difficulties in learning mathematics is not only determined by cognitive aspects, but is also influenced by affective dimensions, especially self-compassion which plays a role in managing emotions and adaptive responses to failure. This study aims to analyze the relationship between self-compassion and mathematical resilience in mathematics education students. This study used a quantitative approach with a correlational design on 40 participants selected through simple random sampling. Data were collected using a Likert scale questionnaire and analyzed through descriptive statistics and Spearman's correlation test. The results showed that the average self-compassion (M = 58.45; SD = 6.861) and mathematical resilience (M = 57.03; SD = 7.127) were in the moderate category. The correlation test showed a positive, strong, and significant relationship between the two variables (rₛ = 0.728; p = 0.000). These findings indicate that self-compassion plays an important role in strengthening students' mathematical resilience. Therefore, the development of self-compassion needs to be integrated into mathematics learning as a strategy to increase students' resilience in facing learning difficulties.